How ESG Practices Reshape the Corporate value of Luxury Electric Vehicles - Evidence from Porsche AG - Peng Ruoyao (SHS Web of Conferences, 2025)
As the global climate change challenge intensifies and electric vehicle technology becomes more sophisticated, the impact of ESG practices on the value of new energy vehicle (EV) companies is in the spotlight. Using Porsche AG as a case study, this study qualitatively analyses how ESG initiatives are reshaping the value of luxury electric vehicle companies through Porsche AG’s Annual and Sustainability Report (2022-2024). During the 2022-2024 period, the company augmented its value by investing in sustainable technological innovations, implementing an environmental management system across its supplier network, and issuing green bonds. The findings suggest that ESG practices have a positive effect on Porsche’s corporate value, shedding light on the green transformation of luxury automobile companies. It also provides meaningful reference for the government issuing more efficient policies on how to encourage ESG practices.